Research and application of water drainage borehole design method based on three-dimensional geological model - Zhenrong WANG (Meikuang Anquan, 2025)
In order to address the issues of low efficiency, insufficient visualization, and inadequate utilization of three - dimensional geological information in the design of mine water drainage boreholes, a design method for water drainage boreholes is proposed based on a three - dimensional geological model, by comprehensively applying technologies such as spatial topology relationships and spatial geometric algorithms. Firstly, using mine geological and surveying data, a detailed three - dimensional model including geological bodies such as roadways, coal seams, aquifers, abnormal areas, and water - filled areas is constructed with the help of three - dimensional geological modeling technology. The mine roadway model is reconstructed through the roadway centerline with three - dimensional coordinates and relevant attributes; the coal seam model is constructed by triangulating point data and boundary data, and is dynamically updated based on the cross - layer point data during borehole construction; the hydrogeological model is constructed by processing spatial data points using the Delaunay triangulation algorithm, similar to the coal seam modeling method, and is also updated according to the control point data collected during borehole construction. In terms of borehole parameter calculation, three typical design modes are provided. When the starting and ending point plane coordinates of the borehole are known, all parameters can be calculated; when the starting point of the borehole, the target horizon and other conditions are known, all parameters can be calculated; when the starting point, the target horizon plane coordinates and other conditions are known, all parameters can also be calculated. These calculation processes adopt algorithms such as the intersection calculation of rays and triangular meshes to ensure the accuracy of the intersection of the borehole trace line and the stratum model, thus ensuring that the borehole can accurately pass through the exploration and drainage target. An integrated water drainage borehole design system is developed, realizing functions such as borehole parameter design, borehole management, deviation analysis, and three - dimensional visualization. This system was applied in the 22308 working face of Halagou Coal Mine in Shendong Mining Area. Relevant geological models were constructed, and 9 water drainage boreholes were designed using design mode II, with parameters such as horizontal distance, vertical distance, and inclined length calculated. The application results show that compared with manual design, based on the three - dimensional geological model, technicians only need to determine the plane position of the borehole and select the appropriate design function to quickly obtain all borehole parameters and achieve three - dimensional visualization. The design efficiency is significantly improved, the accuracy is remarkably enhanced, and the design results are more reliable, providing strong technical support for the prevention and control of mine water hazards.